The witch of portobello - Coelho, Paulo (New York Harper Collins, 2008)
That is the central question of international bestselling author Paulo Coelho's profound new work, The Witch of Portobello. It is the story of a mysterious woman named Athena, told by the many who knew her well - or hardly at all. Like The Alchemist, The Witch of Portobello is the kind of story that will transorfm the way readers think about love, passion, joy, and sacrifice